A multicentre study to determine the value and safety of drug patch tests for the three main classes of severe cutaneous adverse drug reactions. (28th February 2013) - Barbaud, A.; Collet, E.; Milpied, B.; Assier, H.; Staumont, D.; Avenel‐Audran, M.; Grange, A.; Amarger, S.; Girardin, P.; Guinnepain, M.‐T.; Truchetet, F.; Lasek, A.; et al.
Summary Background Drug patch tests (PTs) can reproduce delayed hypersensitivity to drugs and entail a moderate re‐exposure of patients to offending drugs. Objectives To determine the value of PTs for identifying the responsible drug in severe cutaneous adverse drug reactions (SCARs) such as acute generalized exanthematous pustulosis (AGEP), drug reaction with eosinophilia and systemic symptoms (DRESS) and Stevens–Johnson syndrome/toxic epidermal necrolysis (SJS/TEN). Methods In a multicentre study, PTs were conducted on patients referred for DRESS, AGEP or SJS/TEN within 1 year of their SCAR. All drugs administered in the 2 months prior to and the week following the onset of the SCAR were tested. Results Among the 134 patients included (48 male, 86 female; mean age 51·7 years), positive drug PTs were obtained for 24 different drugs. These included positive tests for 64% (46/72) of patients with DRESS, 58% (26/45) of those with AGEP and 24% (4/17) of those with SJS/TEN, with only one relapse of AGEP. The value of PTs depended on the type of drug and the type of SCAR (e.g. carbamazepine was positive in 11/13 DRESS cases but none of the five SJS/TEN cases). PTs were frequently positive for beta lactams (22 cases), pristinamycin (11 cases) and in DRESS with pump proton inhibitors (five cases), but were usually negative for allopurinol and salazopyrin. Of 18 patients with DRESS, eight had virus reactivation and positive PTs. In DRESS, multiple drug reactivity was frequent (18% of cases), with patients remaining sensitized many years later. Conclusions PTs are useful and safe for identifying agents inducing SCAR.